Islamic stock market: current state and prospects of development. (Journal of Economic Research & Business Administration, 2015)
Stock markets in many countries are currently experiencing some difficulties related to the decline in free cash flow, limiting the number of participants in the stock market, with the instability of activities of individual players and the world’s stock markets etc. In this regard, particular interest is currently an Islamic stock market, which has about 200-250 Islamic funds actively investing in international stocks and bonds. Thus, in this research paper analyzes the current state of Islamic stock market, which has its own distinctive features that are built on the principles of the Islamic religion, but nevertheless successfully operating in many world stock markets, the proposed classification of the alleged Islamic mutual funds. Also in a paper developed by the author offers promising directions for further development of Islamic stock market, namely the need to develop a set of measures to reduce market segmentation and its consequences; introduction of guarantees execution of contracts and the protection of investors, to develop products that could be used by Islamic financial institutions, the creation of favorable from the point of view of the principles of Sharia infrastructure.
Keywords: Islamic finance; Islamic stock market; Islamic securities; Islamic bonds; Islamic mutual funds; sukuk